Deep learning in practice - Ghayoumi, Mehdi (Boca Raton: CRC Press, 2022)
"Deep Learning in Practice helps you learn how to develop and optimize a model for your projects using Deep Learning (DL) methods and architectures. This book is useful for undergraduate and graduate students, as well as practitioners in industry and academia. It will serve as a useful reference for learning deep learning fundamentals and implementing a deep learning model for any project, step by step"--
"A Chapman & Hall book."
Includes bibliographical references (pages 189-193) and index.
Keywords: Deep learning (Machine learning)